Industrial Analysis on Critical Minerals in Indonesia towards the EV and Clean Energy Sector - Chisilia Zahara, Nova; Mussry, Jackie (DINASTI RESEARCH, 2025)
Indonesia has abundant reserve of critical minerals commodity especially those which required for EV and clean energy development. According to Ministry of Energy and Mineral Resources Decree no. 296.K/MB.01/MEM.B/2023, at least 47 minerals are classified as critical. This regulation defines critical minerals as elements and/or minerals required in enormous quantities for strategic industries. At least 20 commodities listed as a strategicminerals. Four of them will be examined in this academic paper to get a comprehensive perspective regarding its opportunity towards EV and clean energy sector in Indonesia. These are nickel, bauxite, copper, and tin. The method will be utilized are Porter’s Five Forces and Market Analysis. These aimed to identify Indonesia’s position among the global market and to get detail knowledge regarding each commodity. As the only holding mining company in Indonesia, MIND ID mandated to accelerate the development of critical mineral industry especially commodities required in producing EV and clean energy equipment.